O sonhar compartilhado em análise: vicissitudes da rêverie no encontro analítico - Pinheiro, Carolina Paixão de Albuquerque (2022)
Based on selected clinical cases and vignettes, the research aims to understand and justify in theoretical and metapsychological terms the occurrence of mental images in the analyst's listening. At first, the thesis questions whether the images can be considered rêveries, according to the concept originally proposed by Bion. Authors such as Ogden, Ferro and Civitarese increase the recognition and understanding of the clinical phenomenon of reverie in the unconscious communications between analysand and analyst, with the concept of the analytic third and the theoretical-clinical formulations of the post-bionian analytic field. The aim is to understand in which way the intersubjective exchanges facilitate processes of symbolization and expansion of conscious and unconscious psychic work, through the images evoked by the encounter. With authors such as the Baranger and Cassorla, we also aim to analyze whether images can contribute to the formation of shared defenses and resistances, leading to the formation of impasses, baluartes and enactments in the analytic field. Ethical and technical problems about countertransference are addressed, verifying its instrumental potential for clinical management purposes, considering countertransference in terms of use of the analyst (Bollas) and modes of presence between implication and reserve (Figueiredo). The analyst's reserves, constituted not only by her psychoanalytic training, but by her cultivation along with other cultural devices, are in this case considered in terms of photographic reserves that increase the availability of mind and reverie activity. Considering these reserves, are elaborated throughout the thesis poetic and metaphorical articulations between psychoanalytic clinic and photography